Novel magnetic micro-structured porous materials for biomedical applications - Molinar Diaz, Jesus (2023)
Novel, porous and dense, ceramic (Fe3O4 & Ca2Fe2O5) and glass-ceramic (phosphate-based glass matrix with magnetic domains) magnetic microspheres have been manufactured for the first time via a rapid, single-stage, flame spheroidisation process. Morphological, structural, and compositional investigations provide evidence into the microsphere formation mechanisms, as a function of Fe3O4 precursor particle size, precursor-to-porogen mass ratio, and gas flow settings. Optimised conditions for the flame spheroidisation processing of these ceramic and glass-ceramic, porous and dense magnetic microspheres are identified. The magnetic properties of the materials provided for controlled induction heating to a constant level (40 – 45 °C), making these microspheres highly appropriate for localised magnetic hyperthermia applications. Complementary, cytocompatibility investigations confirmed the suitability of porous microspheres for biomedical applications. It is suggested that the flame-spheroidised materials developed opens up new opportunities for the rapid manufacture of innovative synergistic biomaterials, towards magnetic hyperthermia applications.